The question of culture continuity and change after disaster: Further thoughts. Issue 1 (May 2016) - HOFFMAN, SUSANNA M.
Abstract : Anthropologists often struggle with interpreting the extent to which human behavior during and after disasters constitute departures from pre‐existing culture, as the issue is both theoretically poignant but also pragmatically critical. When I first wrote about the concern, I offered that the extent to which disasters cause consequential cultural change is largely determined by size or magnitude of the disaster, whether the manifestations of change are scrutinized in short or long term, and whether the change occurs within the deep structures of a culture or merely surface regalia. I also touched on resistance to change. In the plenary on the issue addressed here, several anthropologists well familiar with the problematics of disaster spoke to the concern anew, and in light of seriously changing global conditions, I, too, had expanded observations to add. They pertain both to general theories of culture continuity and change and to today's altered global situation.